Comparison Of Turkic And Persian Languages In "Boburname" - Qiyomov Farhod Raufovich (Euro Asian Journal Publishing, 2024)
The article provides information on the linguistic features of Babur's work "Boburname", the comparison of Turkish (Uzbek) and Persian-Tajik languages.
Keywords: Boburname; public sources; tablets; Turkic languages